The Development and Measurement of Block Construction in Early Childhood: A Review. (27th July 2019) - Tian, Mi; Luo, Tianrui; Cheung, Him
Children's block building has long been a focus of psychological research, in part because block building skills are thought to be useful indicators of other abilities such as representational thinking. Block building skills are assumed to progress through developmental stages and a number of measures have been developed to assess these skills. In this article, we critically review the literature on two topics related to children's block building. First, we examine the literature on developmental changes in block play with a focus on the approximate age trends for various block construction abilities. Second, we provide an overview of the scales used to assess block construction complexity such as the Block Building Measure, Building Performance Coding, and Block Structure Complexity Scoring Instrument and propose a conceptual model of the skills involved in block building. Based on this review, we recommend ways to refine existing research methods, improve scale validity, and combine different indices to establish a more comprehensive measure of children's block construction.